Race, ethnicity and law - Deflem, Mathieu (Sociology of crime, law and deviance, 2017)
"Addresses issues of race and ethnicity within the law and law-related phenomena. In today's so-called multicultural, post-racial world racial and ethnic concerns prevail in many aspects of modern law. Contributors to this volume examine racial and ethnic disparities in sentencing and punishment; the continued problematic nature of the African American experience within the US system; the criminalization of immigrants; racial inequities in the administration of drug laws; and the racial disparities that affect juvenile justice"--Publisher's description